Simulation of water tree distribution in medium voltage power cable insulation model in MATLAB/simulink - Hussain, N. (IEEE Computer Society, 2014)
Water tree degradation is categorized as a pre breakdown mechanism associated with Medium voltage (MV) power insulation failure. It is a slow degradation process, which turns into deterioration of dielectric properties of the cable insulation. The presence of water trees in cable insulation causes the generation of harmonic current components in the loss current. The water tree distribution in varying portions of the cable insulation has been modeled and simulated by utilizing MATLAB/Simulink in this study. The water tree degraded portion in the cable insulation was modeled by utilizing a nonlinear equation. In order to examine the frequency dependence on induced water tree degradation, two different test techniques were utilized in MATLAB/Simulink. Namely, the 3rd harmonic current-based method and the series resonant-based test method. In the first test method, the model was simulated by 50 Hz to 150 Hz by a step increase of test frequency by 25 Hz. The series resonant test method was utilized to test the water tree degraded cable insulation model; the test setup consisted of an inductor (L). The test was implemented by a variable frequency of 0 to 1000 Hz. The results of both test techniques show that the water tree distribution in varying cable insulation lengths can be quantified precisely. Â© 2014 IEEE.